(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
in the management of the entertainment tax in the Department of Revenue of Manado is the level of awareness of taxpayers who pay taxes are still low in entertainment, still less employees in dealing with the entertainment tax and lack of socialization to the taxpayer itself This study uses descriptive qualitative approach through in-depth interviews to 9 informants, observation and search for additional documents in the form of a list of guidelines for the interview, a tape recorder and stationery. The results showed that the effectiveness of Management of Entertainment Tax On Revenue Office of Manado City has not been effective. Keywords: Effectiveness of Management of Entertainment Tax